Abalone farm discharges the withering syndrome pathogen into the wild - Lafferty, Kevin; Ben-Horin, Tal (Frontiers in Microbiology, 2013)
An intracellular bacterium Candidatus Xenohaliotis californiensis, also called Withering-Syndrome Rickettsia-Like Organism (WS-RLO), is the cause of mass mortalities that are the chief reason for endangerment of black abalone (Haliotis cracherodii). Using a real-time PCR assay, we found that a shore-based abalone farm in Santa Barbara, California, discharged WS-RLO DNA into the ocean. Several other shore-based abalone farms discharge effluent into critical habitat for black abalone in California and this might affect the recovery of wild black abalone. Existing regulatory frameworks exist that could help protect wild species from pathogens released from shore-based aquaculture.